2001
DOI: 10.1073/pnas.211439798
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the central region of bovine fibrinogen (E 5 fragment) at 1.4-Å resolution

Abstract: The high-resolution crystal structure of the N-terminal central region of bovine fibrinogen (a 35-kDa E 5 fragment) reveals a remarkable dimeric design. The two halves of the molecule bond together at the center in an extensive molecular ''handshake'' by using both disulfide linkages and noncovalent contacts. On one face of the fragment, the A␣ and B␤ chains from the two monomers form a funnel-shaped domain with an unusual hydrophobic cavity; here, on each of the two outer sides there appears to be a binding s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
84
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(85 citation statements)
references
References 44 publications
1
84
0
Order By: Relevance
“…Furthermore, they subsequently showed (42) that the third pH-dependent site was present in human FG (K d ∼ 9 × 10 -6 M) only when the AR-chains were intact, suggesting that it could be, for symmetry reasons, a composite site involving the two halves of the molecule. In addition, no Ca 2+ ions were found in the recently published FG central E domain structure (80), although it lacked residues AR1-28 and B 1-60. In the end, a consensus exists only for the two high-affinity Ca 2+ -binding sites, which were clearly localized in the FG outer D domains (5-8), confirming previous biochemical work (see ref 35, and references therein).…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, they subsequently showed (42) that the third pH-dependent site was present in human FG (K d ∼ 9 × 10 -6 M) only when the AR-chains were intact, suggesting that it could be, for symmetry reasons, a composite site involving the two halves of the molecule. In addition, no Ca 2+ ions were found in the recently published FG central E domain structure (80), although it lacked residues AR1-28 and B 1-60. In the end, a consensus exists only for the two high-affinity Ca 2+ -binding sites, which were clearly localized in the FG outer D domains (5-8), confirming previous biochemical work (see ref 35, and references therein).…”
Section: Discussionmentioning
confidence: 88%
“…22) and the bovine fibrinogen E 5 fragment (PDB ID 1JY2; ref. 33) were taken as probe models. The rotation search was conducted in the resolution range of 15-3.65 Å, independently for each model.…”
Section: Data Collection and Processingmentioning
confidence: 99%
“…The disulfide-linked NH 2 -terminal portions of all six chains form the central E region, whereas COOH-terminal portions form two terminal D regions and two ␣C domains (28)(29)(30). Recent x-ray studies of fibrinogen and its fragments established the high-resolution structure of most of the molecule (31)(32)(33)(34). Specifically, it was found that, in the central region, the NH 2 -terminal portions of the A␣͞B␤ chains and the ␥ chain form the funnel-shaped domain on one side of the molecule and the ␥N-domain on the other side, respectively, while the remaining portions of all three chains in both subunits form triple helical coiled coils (33,34).…”
mentioning
confidence: 99%
See 2 more Smart Citations